The Representation of the Image of Russia in Foreign National Mass Media Discourse - O. V. Degtyareva (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2021)
This article focuses on the representation of the image of Russia in the discourse of foreign media (2014–2020). Taking into account the definition of the image of the state as a special concept, the article claims the lexeme «Russia», as well as the identities associated with this image in political and mass-information discourse. This concept contains historical, metaphorical, evaluative, ethnocultural and associative layers. Based on scientific  research on the problems of media discourse, image-formation, associations, and using the methods of critical discourse and conceptual metaphorical analysis, the article reveals the range of means of reaching the concept of «Russia» used by the media. Discourse depends on grammar, semiotics, semantics, structure and argumentation,  therefore it is important to answer the questions: how do «they» speak about «us» and how is the image of «us» formed in text or speech? To achieve the goal, we had content analysis of massmedia and had the associative  experimental technique too. These tools demonstrate the ideological values of the discourse in question and the associations that it forms in the minds of people. The paper suggests that the scheme of analysis of the image of state in the political mass media discourse, offered in it, can be applied to the investigation of images of other states.